A HEURISTIC SCHEDULING ALGORITHM FOR IMPROVING THE DURATION AND NET PRESENT VALUE OF A PROJECT - (:unkn) unknown (MCB UNIV PRESS LTD, 1995)
Proposes a heuristic iterative scheduling algorithm for the resource constrained project scheduling problem. Considers a general model where activities are represented by multiple operating modes and each operating mode is constituted of different activity durations and resource requirements. The performance measures considered are the minimization of project duration and the maximization of net present value (NPV). In the cash flow model assumed, activity expenditures take place at their start times and the project payment is made on its completion. The iterative scheduling algorithm consists of forward/backward scheduling passes, where consecutive scheduling passes are linked by updated activity time windows. The iterative algorithm is supported by a conflict-based activity selection technique called local constraint based analysis (LCBA). A considerable amount of improvement in both performance criteria is observed when the results of the iterative algorithm are compared with the results given by the initial forward schedule.
Keywords: ALGORITHMS; HEURISTICS; NET PRESENT VALUE; PROJECTS; SCHEDULING; RESOURCE CONSTRAINTS; PROGRAMMING APPROACH; CASH FLOWS; MAXIMIZE; BRANCH